City Cemeteries as Cultural Attractions: Towards an Understanding of Foreign Visitors’ Attitude at the National Graveyard in Budapest - Brigitta Pécsek (DETUROPE)
The paper aims to reposition urban cemeteries within the tourism supply and to showcase their values as cultural tourism products that can enrich visitors’ experiences. Although urban cemeteries as ritual meeting points of life and death have become an integral part of city tourism, contemporary tourism literature mostly embeds them in dark tourism or thanatourism, neglecting the experience-rich potentials of cemeteries as cultural products. This paper rectifies this by arguing that cemetery tourism makes a fascinating cultural display for tourists, offering both nature-based and cultural activities, therefore, it can be rightfully placed in heritage and cultural tourism. The paper investigates foreign visitors’ attitude at the National Graveyard in Budapest. During the empirical research 52 questionnaires were correctly filled in, followed by the same number of mini-interviews. The research findings confirmed the initial hypotheses: 1. Visitors regarded cemeteries as complex attractions representing both natural and cultural values, which added to the positive experiences of a Budapest city break. 2. There was no reference to the so called “dark aspects” of cemeteries in the answers. 3. Although the satisfaction rate was high, the lack of visitors is a clear indication that the cemetery in Budapest has been so far undervalued as an urban attraction. On the negative side, respondents criticized the lack of information sources available prior to visit, the inefficient marketing and the undesirable neighbourhood. The paper ultimately aims to provide stakeholders solid, preliminary data that might serve as a launching pad for further larger-scale research.